Peran Humas Rumah Sakit Unand Dalam Mengelola Opini Publik di Media Online - lestari, yayuk (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
This study discusses how public opinion is about Unand Hospital and how is the role of Public Relations of Unand Hospital in managing public opinion in online media. This study uses the public sphere theory by Habermas and the public information model by Grunig and Hunt. The research method used in this study is descriptive qualitative with a positive post paradigm. Data collection techniques used are interviews, observation and documentation. The study results showed many negative and positive opinions emerged from an individual perspective due to interactions with Unand Hospital. Public Relations of Unand Hospital carried out various ways to manage negative public opinion, namely collaborating with local media to divert issues and providing clarification on an issue regarding Unand Hospital to taking three steps to managing public opinion, namely apologizing, verifying identity, providing related explanations complaints from patients to evaluate services to related polyclinics.